2003
DOI: 10.1016/s0006-3495(03)74968-6
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Initiate a Ca2+ Wave in Frog Eggs that is More Similar to Ca2+ Waves Initiated by IP3 than by Ca2+

Abstract: We have measured the initial propagation velocity of the sperm-induced Ca(2+) wave in the egg of Xenopus laevis and have compared it with the initial propagation velocities of the inositol triphosphate (IP(3))-induced and Ca(2+)-induced Ca(2+) waves. The initial mean propagation velocity of the sperm-induced wave (13 microm/s) is very similar to that of the IP(3)-induced waves (12.3 microm/s) and two times faster than the mean Ca(2+)-induced wave velocity (6.6 microm/s). We have generated realistic simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…We have indeed seen above [see section 'An artificial pacemaker site (PM3) is revealed by flash-photolysis of Ins(1,4,5)P3 or gPtdIns(4,5)P2'] that Ins(1,4,5)P3 appears to be a local messenger that cannot, through a single increase, induce repetitive Ca 2+ rises. By contrast, a theoretical study of the fertilization Ca 2+ wave in Xenopus oocyte (Bugrim et al, 2003) concludes that an elevated concentration of Ins(1,4,5)P3 near the site of fertilization appears as the most probable mechanism to reproduce the experimental observations. The contradiction between the latter theoretical results and ours can be explained by the fact that the study for Xenopus oocytes simulates the unique fertilization wave as a switch between a stable state with low cytosolic Ca 2+ and another stable state with a high cytosolic Ca 2+ .…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…We have indeed seen above [see section 'An artificial pacemaker site (PM3) is revealed by flash-photolysis of Ins(1,4,5)P3 or gPtdIns(4,5)P2'] that Ins(1,4,5)P3 appears to be a local messenger that cannot, through a single increase, induce repetitive Ca 2+ rises. By contrast, a theoretical study of the fertilization Ca 2+ wave in Xenopus oocyte (Bugrim et al, 2003) concludes that an elevated concentration of Ins(1,4,5)P3 near the site of fertilization appears as the most probable mechanism to reproduce the experimental observations. The contradiction between the latter theoretical results and ours can be explained by the fact that the study for Xenopus oocytes simulates the unique fertilization wave as a switch between a stable state with low cytosolic Ca 2+ and another stable state with a high cytosolic Ca 2+ .…”
Section: Discussionmentioning
confidence: 86%
“…It was shown that the correct shape of the fertilization wave in Xenopus oocyte can be reproduced by assuming that Ins(1,4,5)P3 is locally generated at the fertilization site (Bugrim et al, 2003). Moreover, these studies emphasize the role of the spatial inhomogeneities in the ER distribution (Bugrim et al, 2003;Hunding and Ipsen, 2003), in the Ins(1,4,5)P3Rs distribution (Bugrim et al, 2003) or in Ins(1,4,5)P3 production (Wagner et al, 1998) to reproduce the experimentally observed spatial profiles. None of these studies, however, deals with repetitive Ca 2+ waves, as those observed at fertilization of many species, including ascidians and mammals.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations